Perilaku Altruis Relawan Organisasi AbdA di Tinjau dari Tingkat EQ dan SQ - Linda Tri Sulawati (UIN Sunan Kalijaga, 2017)
The lack of prososial behavior among students, prevents them from performing their role as agent of change ang agent of control in the middle of society. Mainstreaming IQ as an indicator of intelligence and succes contributes to the occurrurrence of student apathy behavior. To counteract the phenomenon, need positive psychology-based research to though the excavation of prososial values, especially altruism and promote it among strudents. Researchers use mix method approach with sequensial explanatory aimed to test and understand the role of emotional intelligence and spiritual intelligence to build altruis behavior, especially in organization Aku berada di jalan Allah (AbdA), namely a voluntary organization created by a students who is famous for their activities in the field of orphan welfare in all the orphanages in Tulungagung. the results of the research of 35 volunteer studied showed that the level of EQ and SQ quantitatively influential in forming altruist behavior of AbdA’s volunteers. Qualitative research results also clarify and broaden the understanding of the relevance of EQ and SQ influence in altruist behavior of volunteers.